GAMBARAN HEMOGLOBIN IBU HAMIL DI UPTD PUSKESMAS III DINAS KESEHATANKECAMATAN DENPASAR UTARA TAHUN 2022 - Komang Maytha Indira Suari; I Nyoman Gede Suyasa; I Gusti Agung Ayu Putu Swastini (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Background: Hemoglobin deficiency in pregnant women is one of the health issues that can occur during the pregnancy. Anemia is more common in pregnant women because they require more oxygen, which causes an increase in erythropoietin production. The risk of anemia is connected to hemoglobin levels in pregnant women, with hemoglobin levels of less than 11 g/dl being classified low. Premature labor, miscarriage, extended labor, uterine atony, hemorrhage, and shock are all risks of anemia during pregnancy. Methods: The study used a descriptive design with a sample population of 34 pregnant women. Results: Hemoglobin levels in 22 pregnant women (64.7%) were relatively low, with the majority of them coming onto an age category of not at risk 18 people (81.8%), second trimester age 9 pregnant women (40.9%), pregnancy distance 13 pregnant women (59.1%), and parity 16 pregnant women (72.7%). Conclusion: The majority of pregnant women at UPTD PUSKESMAS III North Denpasar District Health Office have low hemoglobin levels.